Influence of apparently negative personality characteristics on the long-term outcome of health anxiety: Secondary analysis of a randomized controlled trial. - Tyrer,P; Wang,D; Tyrer,H; Crawford,M; Loebenberg,G; Cooper,S; Barrett,B; Sanatinia,R (Personality and Mental Health: multidisciplinary studies from personality dysfunction to criminal behaviour, 2021)
BACKGROUND: It is known that personality has an influence on the outcome of mental state disorders, but detailed studies on its long-term impact are few. We examined the influence of personality status on the 8-year outcome of health anxiety and its relationship to the effects of cognitive behaviour therapy in a randomized controlled trial. AIMS: This study aims to examine both the usefulness of the diagnosis of personality disorder and an additional measure of pathological dependence, in predicting the outcome of medical patients with health anxiety treated with cognitive behaviour therapy. Because the influence of personality is often shown in the long term, these assessments covered the period of 8 years after randomization. An additional aim is to examine the costs of different levels of personality dysfunction in each treatment group. METHOD: Personality dysfunction, using both ICD-10 and ICD-11 classifications of severity, was assessed at baseline by interview in a randomized controlled trial. Patients were also assessed for pathological dependence using the Dependent Personality Questionnaire, also scored along a severity dimension. Four hundred forty-four patients from medical clinics with pathological health anxiety were treated with a modified form of cognitive behaviour therapy for health anxiety (CBT-HA) or standard care. Total costs over follow-up were calculated from hospital data and compared by personality group. RESULTS: At baseline, 381 (86%) had some personality dysfunction, mainly at the lower level of personality difficulty (not formally a disorder). One hundred eighty four (41%) had a personality disorder. A similar proportion was found with regard to dependent personality. Using the ICD-10 classification, 153 patients (34.6%) had a personality disorder, with 83 (54.2%) having anxious or dependent personality disorder, 20 (13.1%) having an anankastic disorder, but also with 66 (43.1%) having mixed disorder. During initial treatment, those